ANALISIS KAUSALITAS PERDAGANGAN INTERNASIONAL DAN PERTUMBUHAN PASAR SAHAM TERHADAP PERTUMBUHAN EKONOMI DI ASEAN 3 PERIODE TAHUN 2000-2015 - Ridho'ah, Hanifatul Afdholatu; Viphindrartin, Sebastiana; Riniati, Riniati (Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
Economic growth is one of the important indicators used to measure the country's development. The participation of Indonesia, Philippines, and Thailand in an inter-state or ASEAN cooperation encourages economic integration. The existence of economic integration then encourages the existence of international trade and capital inflows from outside the territory of the country. Investment is one of the factors affecting economic growth. International trade and stock market developmnet is one of the factors of economic growth for developed countries, while ASEAN 3 is criticized as a developing country.The purpose of this research is to know the causal relationship between international trade and economic growth. And know the causal relationship between growth of stock market with economic growth in ASEAN 3. This study variables of international trade, stock market growth, and economic growth. The data used are annual panel data from 2000 to 2015. Using Granger causality analysis. The results of the study show a bidirectional linkage between international trade and economic growth and there is no mutual relationship between stock market growth and economic growth in ASEAN 3. Keywords: Economic Growth, International Trade, Stock Market Growth, Granger CausalityJEL classification : C23, F15, O1